2022
DOI: 10.3389/fpsyt.2022.977681
|View full text |Cite
|
Sign up to set email alerts
|

Fear and anxiety related to COVID-19 pandemic may predispose to perinatal depression in Italy

Abstract: The COVID-19 pandemic situation significantly affected the mental health of the general and clinical population. However, few studies investigated which COVID-19-related psychopathological determinants may predispose to perinatal depression. We evaluated the impact of COVID-19 related anxiety and fear on perinatal depression in Italy. We retrospectively screened 184 perinatal outpatients afferent to Perinatal Mental Health outpatient service, during March 2020-March 2021, by administering the Edinburgh Postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
2
12
0
Order By: Relevance
“…Another study assessed the impact of COVID-19-related anxiety and fear on perinatal depression among pregnant women in Italy. The mean FCV-19S and CAS scores were 15.0 and 1.7, respectively [ 39 ]. In our study, the scores of pregnant women were similar and were 14.6 in FCV-19S and 0.6 in CAS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another study assessed the impact of COVID-19-related anxiety and fear on perinatal depression among pregnant women in Italy. The mean FCV-19S and CAS scores were 15.0 and 1.7, respectively [ 39 ]. In our study, the scores of pregnant women were similar and were 14.6 in FCV-19S and 0.6 in CAS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that FCV-19S was associated with a lack of resilience, high-frequency use of maladaptive emotion regulation strategies, and impaired quality of life [ 35 , 36 ]. Furthermore, fear to COVID-19 pandemic was documented to predispose to depression and/or anxiety symptoms among both general and clinical population [ [37] , [38] , [39] ]. Correlation analysis in this study showed that fear of COVID-19 was positively and moderately correlated with anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…The first kind of pathway is feeling extremely scared → prolonged smartphone use → depression, indicating that feeling extremely scared could be associated with depression through the mediating role of prolonged smartphone use. Participants feeling extremely scared may hope to get as much information about the pandemic as possible or seek alleviation of their fear and distress through online activities, such as watching TV, gaming, shopping, and communicating through smartphones (67)(68)(69). Volpe et al observed a rise in problematic internet use, social media addiction, and problematic video gaming during COVID-19.…”
Section: Discussionmentioning
confidence: 99%